The Role of Surface Chemistry on the Toxicity of Ag Nanoparticles. Issue 15 (7th March 2013) - Xiong, Yujie; Brunson, Mark; Huh, Juyoung; Huang, Aaron; Coster, Adam; Wendt, Kristy; Fay, Justin; Qin, Dong
Abstract The role of surface chemistry on the toxicity of Ag nanoparticles is investigated using Saccharomyces cerevisiae yeast as a platform for evaluation. Combining the shape‐controlled synthesis of Ag nanoparticles with a comprehensive characterization of their physicochemical properties, an understanding is formed of the correlation between the physicochemical parameters of nanoparticles and the inhibition growth of yeast cells upon the introduction of nanoparticles into the cell culture system. Capping agents, surface facets, and sample stability—the three experimental parameters that are inherent from the wet‐chemical synthesis of Ag nanoparticles—have a strong impact on toxicity evaluation. Hence, it is important to characterize surface properties of Ag nanoparticles in the nature of biological media and to understand the role that surface chemistry may interplay to correlate the physicochemical properties of nanoparticles with their biological response upon exposure. This work demonstrates the great importance of surface chemistry in designing experiments for reliable toxicity evaluation and in mitigating the toxicity of Ag nanoparticles for their safe use in future commercialization.